International humanitarian law in cyberspace: Ratione materiae, ratione temporis and problem of cyber-attack qualification - S. Y. Garkusha-Bozhko (Цифровое право, 2021)
The purpose of the article is to analyse problems arising from applying the rules of International Humanitarian Law in cyberspace, particularly the problems of ratione materiae and ratione temporis of this branch of Public International Law in cyberspace. The rapid development of cyber technologies that can be used within an armed conﬂict afﬁrm the applicability of this research. The existence of “The Tallinn Manual 2.0” on International Law Applicable to Cyber Operations also conﬁrms the impact of this topic on the modern world. The fact that parties in armed conﬂicts use new technologies in cyberspace does not affect the applicability of IHL rules to such military actions. In the context of this issue, a key question which instigates scientiﬁc discussion is that of which cyber operations are subject to the regulation of the law of cyber armed conﬂicts. The urgent need to study this problem stems from the fact that cyberspace is not an ordinary theatre of war, with the means and methods of warfare used in it being in no way related to the traditional use of armed force; given this quality of cyber operations, it is essential to understand which areas may be subject to IHL. The article analyses two main doctrinal points of view in relation to this problem; as this doctrine (in the context of this issue) also addresses the legal qualiﬁcation of cyber-attacks, the article also raises this topical issue. Based on the results of this analysis, the author concludes that, despite all the evidence of theoretical conclusions regarding the problems under analysis, they still do not seem comprehensive due to the lack of relevant state practice, which needs to be developed.